More than a class act? dilemmas in researching elite school girls' feminist politics. (April 2022) - Charles, Claire; Allan, Alexandra
Feminist scholars have long been concerned with privileged women's activism and engagement with feminist politics and how acts of resistance from privileged subjects might best be understood. In the current moment, we are seeing a reinvigoration of interest in feminist activism particularly from young women, but not necessarily focusing on young women who are positioned as privileged. Simultaneously, there is attention in the sociology of elite schooling to the question of social justice politics in privileged spaces. In this article, we contribute to both of these scholarly conversations by reporting on the feminist activism of three young women attending an elite school in Australia. We argue that these young women's activism/feminist politics need to be understood as a complex entanglement of resistance and reproduction with regard to gender, race and class, and that drawing on recent theorisations influenced by post-humanism in feminist educational research produces fresh insights into researching gender/race/class reproduction by young women in elite educational settings.